2005
DOI: 10.1210/en.2005-0239
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Elevation of Parathyroid Hormone in Mice Reduces Expression of Sclerostin by Osteocytes: A Novel Mechanism for Hormonal Control of Osteoblastogenesis

Abstract: Both chronic excess of PTH, as in hyperparathyroidism, and intermittent elevation of PTH (by daily injections) increase the number of osteoblasts; albeit, the former is associated with bone catabolism and the later with bone anabolism. Intermittent PTH increases osteoblast number by attenuating osteoblast apoptosis, an effect that requires the transcription factor Runx2. However, chronic elevation of PTH does not affect osteoblast apoptosis because it stimulates the proteasomal degradation of Runx2. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
417
5
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 586 publications
(461 citation statements)
references
References 23 publications
29
417
5
10
Order By: Relevance
“…At least some of the positive effects of parathyroid hormone on bone formation have been attributed to its ability to moderately down-regulate sclerostin (32)(33)(34). The inability of Scl-AbI to prevent DEXinduced inhibition of growth is therefore consistent with the findings from a study by van Buul-Offers et al (35), in which they showed that parathyroid hormone was also ineffective at reducing GC-mediated growth inhibition (36).…”
Section: Discussionsupporting
confidence: 77%
“…At least some of the positive effects of parathyroid hormone on bone formation have been attributed to its ability to moderately down-regulate sclerostin (32)(33)(34). The inability of Scl-AbI to prevent DEXinduced inhibition of growth is therefore consistent with the findings from a study by van Buul-Offers et al (35), in which they showed that parathyroid hormone was also ineffective at reducing GC-mediated growth inhibition (36).…”
Section: Discussionsupporting
confidence: 77%
“…As PTH is a known inhibitor of SOST transcription, sclerostin would not be expected to be induced if PTH was the initial driver for elevated bone formation. (72)(73)(74) Indeed, subsequent decline in sclerostin later in disease progression may be attributed to the rising levels of PTH (Figs. 1D and 8B).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, intermittent PTH was found to decrease sclerostin expression in bone by about 50%. (66)(67)(68) In the case of continuous PTH infusion (67) or osteocyte-specific constitutively elevated PTH signaling, (69) the effect was more pronounced, with sclerostin expression being decreased by more than 80%. Experiments using in vitro approaches have shown that PTH can downregulate sclerostin expression through the MEF2 transcription complex in a downstream enhancer region for the sclerostin gene.…”
Section: Osteocytes Mechanical Loading and Interface With The Pth Pmentioning
confidence: 99%